The Management of Additive Manufacturing Enhancing Business Value - Khorram Niaki, Mojtaba (Springer Series in Advanced Manufacturing,, 2018)
This book introduces readers to additive technology and its application in different business sectors. It explores the fundamental impact additive has on technology, particularly on operations, innovation, supply chains, the environment and customer relations. Subsequently, on the basis of a broad survey of the best technology adopters, it offers advice on how to enhance business value by implementing the technology in different industrial and commercial environments. Additive manufacturing (AM) is a new area of manufacturing that has already brought about phenomenal changes to industry and business models. It affects nearly all aspects of the managerial and organizational thinking that was applied to conventional manufacturing. Currently, the technology is being adopted in manufacturing areas that involve high-value products with complex geometries, and small to medium production volumes. It boosts the productivity of new product development processes by slashing costs, reducing time and promoting creativity and innovativeness. Further, it shrinks supply chains by bringing firms closer to their customers. This unique book offers abundant empirical and practical evidence confirming the value of this new technology.